2019
DOI: 10.1186/s40814-019-0454-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Analgesia for Prehospital hip Disruption (RAPID): findings from a randomised feasibility study

Abstract: Background In managing hip fracture, effective pain relief before admission to hospital is difficult without risking side effects. Although emergency departments routinely use fascia iliaca compartment block (FICB), there has been little evaluation of its use by paramedics before hospital admission. We aimed to assess whether a multi-centre randomised trial to evaluate FICB was feasible. Methods Volunteer paramedics used scratchcards to allocate patients with hip fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 69 publications
1
27
0
6
Order By: Relevance
“…FICB is a safe and effective pain management for hip fracture in hospital allowing reduced morphine administration and potentially fewer side effects 20 23 58 59. It can also be administered by paramedics at the scene of injury although evidence of effectiveness in this setting is lacking 19 29 30 58. The RAPID study has demonstrated that paramedics are willing and able to administer FICB to patients with suspected hip fracture before ambulance transport to hospital 60.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FICB is a safe and effective pain management for hip fracture in hospital allowing reduced morphine administration and potentially fewer side effects 20 23 58 59. It can also be administered by paramedics at the scene of injury although evidence of effectiveness in this setting is lacking 19 29 30 58. The RAPID study has demonstrated that paramedics are willing and able to administer FICB to patients with suspected hip fracture before ambulance transport to hospital 60.…”
Section: Discussionmentioning
confidence: 99%
“…A participating emergency paramedic who attended a 999 call and identified a hip fracture in an eligible patient then used a scratchcard42 to randomly allocate the individual to receive FICB (if not contra-indicated) or usual care. Full RAPID results are available 19…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, a policy change was implemented, stipulating that on-call orthopedic clinicians would review prospective hip fracture patients prior to definitive diagnosis once the hip fracture alert was initiated. It has been shown in one clinical trial that paramedics can diagnose hip fractures out of the hospital, with 77% sensitivity [11]. The reliability of paramedic diagnosis is further demonstrated by the successful implementation of the bypass system in the South-East of Ireland where suspected hip fracture patients are triaged at the scene and brought directly to an orthopedic trauma center, bypassing potentially closer EDs in which orthopedic services are not directly available on site [12].…”
Section: Discussionmentioning
confidence: 99%